Hospital clones of methicillin-resistant Staphylococcus aureus are carried by medical students even before healthcare exposure. Issue 1 (December 2017) - Orlin, Ido; Rokney, Assaf; Onn, Avi; Glikman, Daniel; Peretz, Avi
Abstract Background Methicillin-resistantStaphylococcus aureus (MRSA) strains are prevalent in healthcare and the community. Few studies have examined MRSA carriage among medical students. The aim of this study is to examineStaphylococcus aureus (SA) carriage, and particular MRSA, over time in cohort medical students Methods Prospective collection of nasal swabs from medical students in Israel and assessment of SA carriage. Three samples were taken per student in preclinical and clinical parts of studies. Antibiotic susceptibilities were recorded and MRSA typing was performed by staphylococcal cassette chromosomemec (SCCmec ) types, Panton Valentine Leukocidin (PVL) encoding genes, andspa types. Clonality was assessed by pulsed-field gel electrophoresis. Results Among 58 students, SA carriage rates increased from 33% to 38% to 41% at baseline (preclinical studies), 13 and 19 months (clinical studies), respectively (p  = 0.07). Methicillin-susceptible SA (MSSA) carriage increased in the clinical studies period (22 to 41%, p  = 0.01). Overall, seven students (12%) carried 13 MRSA isolates. MRSA isolates were PVL negative and were characterized as SCCmec II-t002, SCCmec IV-t032, or t12435 with untypable SCCmec . MRSA carriage during the pre-clinical studies was evident in 4/7 students. Two students carried different MRSA clones at various times and persistent MRSA carriage was noted in one student. Simultaneous carriage of MRSA and MSSA was not detected. Conclusions MSSA carriage increased during the clinical part of studies in Israeli medical students. Compared with previous reports, higher rates of MRSA carriage were evident. MRSA strains were genotypically similar to Israeli healthcare-associated clones; however, carriage occurred largely before healthcare exposure, implying community-acquisition of hospital strains.